2021
DOI: 10.1186/s12951-020-00753-9
|View full text |Cite|
|
Sign up to set email alerts
|

Graphene-modified CePO4 nanorods effectively treat breast cancer-induced bone metastases and regulate macrophage polarization to improve osteo-inductive ability

Abstract: Background Breast cancer bone metastasis has become one of the most common complications; however, it may cause cancer recurrence and bone nonunion, as well as local bone defects. Methods Herein, In vitro, we verified the effect of bioscaffold materials on cell proliferation and apoptosis through a CCK8 trial, staining of live/dead cells, and flow cytometry. We used immunofluorescence technology and flow cytometry to verify whether bioscaffold mate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 42 publications
(49 reference statements)
0
36
0
Order By: Relevance
“…However, periodontitis was reported that can suppress the alveolar bone healing via disturbing osteogenic and osteoclastic balance resulting in the loss of teeth [ 30 ]. Macrophages have been reported to be phenotypically plastic and can be activated into reparative M2-like macrophages [ 31 ], which can promote osteoblast differentiation while inhibiting osteoclast formation [ 32 , 33 ]. Therefore, gaining further insights into the mechanisms of reparative M2 macrophages-induced osteoprotective effect will be of great significance for the treatment of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, periodontitis was reported that can suppress the alveolar bone healing via disturbing osteogenic and osteoclastic balance resulting in the loss of teeth [ 30 ]. Macrophages have been reported to be phenotypically plastic and can be activated into reparative M2-like macrophages [ 31 ], which can promote osteoblast differentiation while inhibiting osteoclast formation [ 32 , 33 ]. Therefore, gaining further insights into the mechanisms of reparative M2 macrophages-induced osteoprotective effect will be of great significance for the treatment of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…The plasticity and importance of macrophages in the process of bone repair make them a potential regulatory target for promoting bone repair ( He et al, 2020 ). Some studies have reported that some angiogenic factors are secreted by macrophages ( Ge et al, 2021 ). For example, M1 macrophages can secrete VEGF and promote the germination and extension of blood vessels ( Luo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A bioactive multifunctional CePO4/CS/GO scaffold--formed by the combination of graphene oxide (GO) nanoparticles, CePO4 nanobars and bioactive chitosan (CS)--shows characteristics of photothermal therapy in killing tumors, generating macrophage polarization, promoting blood vessels formation, and induction of bone formation. This scaffold may become a promising platform for the treatment of breast cancer bone metastases by destroying residual bone tumor cells after photothermal therapy and subsequent healing of the bone defects (12). Similarly, graphene oxide (GO) nanocomposites, loaded with superparamagnetic iron oxide nanoparticles spliced with polyethylene glycol (PEG) and grafted with methotrexate and stimulus-sensitive linkers (GO-SPION-MTX), have been developed for photothermal and chemotherapy of breast cancer.…”
Section: Graphene In Breast Cancermentioning
confidence: 99%